2014
DOI: 10.1262/jrd.2013-129
|View full text |Cite
|
Sign up to set email alerts
|

<i>KISS1</i> Gene Expression in the Developing Brain of Female Pigs in Pre- and Peripubertal Periods

Abstract: Puberty is associated with an increase in gonadotropin secretion as a result of an increase in gonadotropin-releasing hormone (GnRH) secretion. Kisspeptin is considered to play a key role in puberty onset in many mammalian species, including rodents, ruminants and primates. The present study aimed to determine if changes in hypothalamic expression of the KISS1 gene, encoding kisspeptin, are associated with the onset of puberty in pigs. The animals (n=4 in each group) were perfused with 4% paraformaldehyde at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…The expression of kisspeptin in the ARC was correlated to the age-related increase in LH pulses, suggesting that kisspeptin neurons in this region of the hypothalamus are critical for the pubertal transition in gonadotropin secretion of sheep. This contrasts with the gilt in which the expression of the kisspeptin gene in the PeV region of the hypothalamus was undetectable, by in situ hybridization, during pubertal maturation (from 0 to 5 months of age) (Ieda et al, 2014). Robust expression of the kisspeptin gene in the ARC of these gilts was observed, but the ARC expression of kisspeptin did not differ with age or puberty status.…”
Section: Oestrogen Feedback and Expression Of Kisspeptincontrasting
confidence: 71%
See 1 more Smart Citation
“…The expression of kisspeptin in the ARC was correlated to the age-related increase in LH pulses, suggesting that kisspeptin neurons in this region of the hypothalamus are critical for the pubertal transition in gonadotropin secretion of sheep. This contrasts with the gilt in which the expression of the kisspeptin gene in the PeV region of the hypothalamus was undetectable, by in situ hybridization, during pubertal maturation (from 0 to 5 months of age) (Ieda et al, 2014). Robust expression of the kisspeptin gene in the ARC of these gilts was observed, but the ARC expression of kisspeptin did not differ with age or puberty status.…”
Section: Oestrogen Feedback and Expression Of Kisspeptincontrasting
confidence: 71%
“…During sexual maturation in the ewe, messenger RNA (mRNA) for kisspeptin is expressed in the discrete region of the periventricular (PeV) nucleus (Redmond et al, 2011a). Similarly, kisspeptin gene expression is found in the PeV of sexually mature and developing gilts (Tomikawa et al, 2010;Ieda et al, 2014). This is a similar area as the AVPV in mice and may be important for GnRH secretion controlling ovulation in pigs.…”
Section: Structural Organization Of Kisspeptin Neurons In the Hypothamentioning
confidence: 99%
“…One study in pigs (Ieda et al 2014) found that KISS1 mRNA levels in the arcuate nucleus did not change Journal of Endocrinology across puberty. By contrast, there is evidence that, in the sheep, kisspeptin expression increases across puberty.…”
Section: Pubertymentioning
confidence: 99%
“…Increased KISS1 expression in the early stages of puberty has been observed in both male and female monkeys and rats (Bentsen et al, 2010; Shahab et al, 2005; Takase et al, 2009). No change in KISS1 expression was observed in the ARC of female pigs across puberty (Ieda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%